2020
DOI: 10.20527/dentino.v5i2.8946
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF KARAMUNTING LEAF EXTRACT (Melastoma malabathricum L.) ON GLUCOSYLTRANSFERASE ENZYME OF Streptococcus mutans

Abstract: Background: Karamunting leaf extract has secondary metabolite compounds such as tannin, flavonoid, and phenol that have antibacteria potential to be used as an alternative to mouthwash in addition to Chlorhexidine 0.12% to lower the incidence of tooth caries. Caries is caused by several important virulence factors, including Streptococcus mutans Glucosyltransferase (GTF) enzyme. Karamunting leaf extract can inhibit the work of GTF enzyme by precipitating, denaturing protein and damaging cell walls. Inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The cytoplasmic membrane becomes damaged and semipermeable, causing leakage of cell components so that the bacterial cell dies. 17 The conclusion of this study is that ramania leaf extract (Bouea macrophylla griff) has antibacterial activity against Actinomyces spp. bacteria, so it has the potential to be used as an alternative material to support root canal irrigation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The cytoplasmic membrane becomes damaged and semipermeable, causing leakage of cell components so that the bacterial cell dies. 17 The conclusion of this study is that ramania leaf extract (Bouea macrophylla griff) has antibacterial activity against Actinomyces spp. bacteria, so it has the potential to be used as an alternative material to support root canal irrigation.…”
Section: Discussionmentioning
confidence: 91%
“…This causes damage to the lipid structure of the DNA of the bacterial cell nucleus, resulting in inhibition of the development or growth of bacteria, and cell death. 7,17 Steroid compounds in ramania leaf extract function as antibacterials, namely by binding to cell phospholipid membranes that have permeable properties to lipophilic compounds, causing the membrane strength to decrease and causing damage to the cytoplasmic membrane of bacterial cells. 15,18 Similar to steroids, chlorhexidine gluconate 2% also has the ability to damage the cytoplasm of bacterial cells, namely by the interaction between the positive charge of the chlorhexidine molecules against the negatively charged bacterial cell wall, which then causes penetration into the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan hasil penelitian yang diperoleh dapat diketahui bahwa ekstrak daun karamunting (Rhodomyrtus tomentosa (Aiton) Hassk.) dapat digunakan sebagai antibakteri alami pengganti antibiotik untuk menyebuhkan penyakit karies gigi (29).…”
Section: Rendemenunclassified
“…14,15 Based on the side effects of chlorhexidine above, a new method is needed to prevent periodontitis with fewer side effects, namely using herbal plants. 16 The use of plants as medicine has long been known, one of the plants that has antibacterial power because of it's biologically active content, namely tamarind leaf (Tamarindus indica L.). [17][18][19] Previous research also reported that ethanol extract of tamarind leaf was proven to have an antibacterial effect against several types of bacteria.…”
Section: Introductionmentioning
confidence: 99%